Association of Iatrogenic Infarcts With Clinical and Cognitive Outcomes in the Evaluating Neuroprotection in Aneurysm Coiling Therapy Trial. (5th April 2022) - Ganesh, Aravind; Goyal, Mayank; Wilson, Alexis T.; Ospel, Johanna Maria; Demchuk, Andrew M.; Mikulis, David; Poublanc, Julien; Krings, Timo; Anderson, Roberta; Tymianski, Michael; Hill, Michael D.; ,
Abstract : Background and Objectives: Small iatrogenic brain infarcts are often seen on diffusion-weighted MRI (DWI) following surgical or endovascular procedures, but there are few data on their clinical effects. We examined the association of iatrogenic infarcts with outcomes in the ENACT (Evaluating Neuroprotection in Aneurysm Coiling Therapy) randomized controlled trial of nerinetide in patients undergoing endovascular repair of intracranial aneurysms. Methods: In this post hoc analysis, we used multivariable models to evaluate the association of the presence and number of iatrogenic infarcts on DWI with neurologic impairment (NIH Stroke Scale [NIHSS]), functional status (modified Rankin Scale [mRS]), and cognitive and neuropsychiatric outcomes (30-minute test battery) at 1–4 days and 30 days postprocedure. We also related infarct number to a z score–derived composite outcome score using quantile regression. Results: Among 184 patients (median age 56 years [interquartile range (IQR) 50–64]), 124 (67.4%) had postprocedural DWI lesions (median 4, IQR 2–10.5). Nerinetide treatment was associated with fewer iatrogenic infarcts but no overall significant clinical treatment effects. Patients with infarcts had lower Mini-Mental State Examination (MMSE) scores at 2–4 days (median 28 vs 29, adjusted coefficient [acoef] −1.11, 95% CI −1.88 to −0.34, p = 0.005). Higher lesion counts were associated with worse day 1 NIHSS (adjusted odds ratio for NIHSS ≥1: 1.07, 1.02–1.12, p = 0.009), day 2–4 mRS (adjusted common odds ratio [acOR] 1.05, 1.01–1.09, p = 0.005), and day 2–4 MMSE (acoef −0.07, −0.13 to −0.003, p = 0.040) scores. At 30 days, infarct number remained associated with worse mRS (acOR 1.04, 1.01–1.07, p = 0.016) and Hopkins Verbal Learning Test (HVLT) delayed recall scores (acoef −0.21, −0.39 to −0.03, p = 0.020). Patients with infarcts trended towards lower 30-day Digit Symbol Substitution Test (DSST) scores (acoef −3.73, −7.36 to −0.10, p = 0.044). Higher lesion count was associated with worse composite outcome scores at both 1–4 days and 30 days (30-day acoef −0.12, 95% CI −0.21 to −0.03, p = 0.008). Among those with infarcts, day 1 NIHSS and day 2–4 mRS correlated with 30-day NIHSS, DSST, HVLT, and mRS scores, whereas day 2–4 MMSE correlated with 30-day NIHSS and DSST scores (Spearman ρ 0.47, p = 0.001). Discussion: Iatrogenic brain infarcts were associated with subtle differences in postprocedural (1–4 days) and 30-day outcomes on different measures in this middle-aged cohort, with earlier dysfunction correlating with later differences. Trial Registration Information: Clinical trials registration NCT00728182.